PENGARUH KOMUNIKASI PERSUASIF GURU DAN DUKUNGAN ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI SISWA KELAS XI SMA SWASTA TELADAN PEMATANGSIANTAR - Rohni Art Saragih; Anton Luvi Siahaan; Paulina Herlina Sirait (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to obtain knowledge about the influence of teacher persuasive communication and parental support on student learning motivation in economics subjects of class XI students of SMA Swasta Teladan Pematangsiantar. This type of research is quantitative research with a quantitative descriptive data analysis approach with the testing media used being SPSS 21. The population in this study was 240 people. The sample collection technique used was 71 people. The sample collection technique used was cluster sampling (a method of taking representatives from each existing region/group). The data collection instruments used were observation, interviews, documentation and questionnaires. Hypothesis data collection techniques use multiple linear regression analysis, T Test, F Test and coefficient of determination (R2). The results of this study state that: 1) Teacher persuasive communication has an effect but is not significant on student learning motivation. This result can be seen in the t test where the t value of teacher persuasive communication (0.669) ˂ (1.990). The significant value obtained by teacher persuasive communication is 0.05. 2) Parental Support (2149) > (1990). The significant value obtained is 0.05 which means that the variable is significant. 3) Teacher persuasive communication and parental support together have an effect and are significant on student learning motivation. This result can be seen in the F test where the F value (2494) > Ftable (3.08). The R Square Determination Coefficient Test is known to be 0.068 which means that 0.068% of the teacher persuasive communication and parental support variables have an effect on student learning motivation.